CAGE18-2 Cruise Report: LoVe site – exploration around node 7 - Ferré, Bénédicte (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2022)
The cruise was conducted from May 20th to 27th 2018 as part of the Centre of Excellence for Arctic Gas Hydrate, Environment and Climate (CAGE) at UiT – The Arctic University of Norway. The main goal of the cruise was to explore the area around Node 7 as part of the LoVe (Lofoten-Vesterålen) observatory. The first phase of the LoVe project was founded by Statoil in was first launched in 2013 to observe a cold coral reef. This area is known to be an oceanographic hotspot because the shelf is very narrow and northern drift of warm Atlantic water is concentrated and very dynamic in this area. It is also a biological hotspot because the large oceanic fish stocks are passing through or spawn in the area. It is finally an economic hotspot because the area is expected to hold large oil and gas resources but exploitation of these resources is controversial because of the importance for fish and fishermen in this region. The observatory has 12 sensors on the platform today including a camera looking at the coral reef and echosounders to study the biology. The second phase of LoVe was granted by the Research Council of Norway in 2015 through the Infrastructure programme, with a network of nodes crossing the main oceanographic and biological processes. The various nodes of the planned transect have specific objectives, and in particular, node 7 is located on top of methane seepages which CAGE is in charge. The present cruise aimed at performing echosounder and multibeam surveys as well as performing water samples and CTD casts around node 7 and known seepage area. The addressed scientific topics include quantification of methane concentration in the water column, temperature and salinity (via CTD casts), echosounder and multibeam signals and current (amplitude and direction) The cruise may be known as: CAGE18_2